2015
DOI: 10.3390/ijerph120911506
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Communication on Social Media and Its Psychological Mechanisms: An Examination of Chinese Microblog Users

Abstract: Background: This study aims to examine the characteristics of people who talk about suicide on Chinese microblogs (referred to as Weibo suicide communication (WSC)), and the psychological antecedents of such behaviors. Methods: An online survey was conducted on Weibo users. Differences in psychological and social demographic characteristics between those who exhibited WSC and those who did not were examined. Three theoretical models were proposed to explain the psychological mechanisms of WSC and their fitness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 62 publications
(68 reference statements)
0
26
0
1
Order By: Relevance
“…In China, Sina Weibo is a microblogging platform that enables Chinese media users to disseminate and acquire information and is mainly used by young people. Many users have expressed suicide ideation and have broadcasted suicide attempts on this social media [ 7 - 11 ]. Included on the platform, Direct Message is another vital method of Chinese microblogging.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Sina Weibo is a microblogging platform that enables Chinese media users to disseminate and acquire information and is mainly used by young people. Many users have expressed suicide ideation and have broadcasted suicide attempts on this social media [ 7 - 11 ]. Included on the platform, Direct Message is another vital method of Chinese microblogging.…”
Section: Introductionmentioning
confidence: 99%
“…They can reach a large audience and influence many people 7 . The literature shows that people with higher risk of suicide are more likely to talk about suicide in blogs 8 . Studies focusing on posts about suicide in blogs are scarce, despite the relevance of this virtual environment 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that people with higher risk of suicide are more likely to talk about suicide in blogs 8 . Studies focusing on posts about suicide in blogs are scarce, despite the relevance of this virtual environment 8,9 . Furthermore, studies focusing on suicidal behavior in bogs have to take into account the inherent sociocultural aspect, and no studies on suicidal posts in Portuguese have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is the leading cause of death among the 15-29 year-old women in Bangladesh [1] and globally it is the second leading cause of death among the youth [2]. This age group is also most active in the social networking sites such as Facebook.…”
Section: Introductionmentioning
confidence: 99%